The Effect of Cladode Drying Techniques on the Prebiotic Potential and Molecular Characteristics of the Mucilage Extracted from Opuntia ficus-indica and Opuntia joconostle - José Manuel Cruz-Rubio; Monika Mueller; Renate Loeppert; Helmut Viernstein; Werner Praznik (MDPI AG, 2020)
The dry, powdered cladodes of Opuntia ficus-indica are often-used in over-the-counter (OTC) pharmaceutical formulations. Gentle drying techniques, such as lyophilization and vacuum drying are compared with convection drying for the cladodes and also compared with another species of economic importance, Opuntia joconostle. The heteropolysaccharide purified from the mucilage extracted from the dried powders were investigated in their monosaccharide composition (HPAEC-PAD, TLC), mineral and protein content, molecular dimensions (SEC) and fermentability by probiotic bacteria (Bioscreen technique) for evaluation of the prebiotic potential of the mucilage. The heteropolysaccharide is composed of galactose, arabinose, xylose, galacturonic acid and rhamnose. O. ficus-indica includes an additional 13% of glucose coming from an α-glucan. The content of Ca (0.3%) and Mg (0.4%) is relatively low in both species; the content of protein adds up to 1.5% in O. ficus-indica but is significantly lower in O. joconostle with 0.8%. The average molecular mass Mw of the extracted mucilage ranges from 3.7 to 4.7 × 105 g∙mol−1 for both species; only the mucilage from long-time convection drying (C2) delivers a lower average Mw of 2.6 × 105 g∙mol−1, due to partial breakdown of the mucilage matrix. All tested probiotic strains utilized the mucilage to some extent; C2 being the most active, and thus confirms the prebiotic potential of cladode's powder and its derived products. In general, the molecular dimensions and prebiotic potential are not extremely sensitive to the drying treatment, yet temperature and drying time can modify the cladode's powder to a profile with better prebiotic characteristics.